Wound healing of dehiscence defects following different root conditioning modalities: An experimental study in dogs - Zandim-Barcelos, Daniela Leal [UNESP]; Leite, Fábio Renato Manzolli; da Silva, Vanessa Camila; Lopes, Beatriz Maria Valério; Spolidorio, Luiz Carlos [UNESP]; Sampaio, José Eduardo Cezar [UNESP] (Springer Nature, 2013)
Objective: The purpose of this study was to investigate the periodontal healing pattern of dehiscence-type defects following different chemical root conditioning modalities. Materials and methods: Buccal osseous dehiscence defects were created on six teeth of seven dogs. After dental plaque accumulation, defects were treated with sterile saline solution (control group) or one chemical conditioning modality: citric acid (CA group), ethylenediaminetetraacetic acid (EDTA group), tetracycline (TTC group), citric acid + tetracycline (CA + TTC group), or tetracycline + citric acid (TTC + CA group). After 3 months of healing, clinical parameters were evaluated, and the animals were killed. Histological sections were processed, and a computer-assisted histometric analysis was used to evaluate the formation of new cementum, new bone, and epithelial apical migration. Results: All treatments yielded significant improvements in terms of probing depth decrease and clinical attachment level gain compared to baseline values; however, without significant differences among the groups (p > 0.05; one-way ANOVA). The highest amount of new cementum was noted in the EDTA group (3.72 ± 0.83 mm, 77.6 %), while the lowest amount of new bone was observed in the TTC group (0.7 ± 0.94 mm, 14.3 %). However, no statistically significant differences could be observed among the groups regarding epithelial apical migration, new cementum, and alveolar bone formation (p > 0.05). Conclusion: Chemical root surface conditioning did not promote any significant improvement in periodontal healing pattern of dehiscence-type defects in dogs. Clinical Relevance: Chemical root surface conditioning after surgical debridement did not promote positive or negative effects on periodontal healing pattern of dehiscence-type defects. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Bone healing; Cementum; Periodontal wound healing; Regeneration; Root surface conditioning